THE ROLE OF TRANSLATION IN GLOBAL LITERARY EXCHANGE (Лучшие интеллектуальные исследования, 2024)
This article examines the crucial role translation plays in facilitating global literary exchange. It argues that translation is not merely a technical process of linguistic conversion but a vital act of cultural mediation, shaping perceptions and expanding access to diverse literary voices. The article analyzes the challenges inherent in literary translation, including the complexities of linguistic nuance, cultural context, and the potential for misrepresentation, while highlighting the significant contributions of translators in bridging cultural divides and enriching global literary landscapes.